Pomegranate (Punica granatum L.) Peel-Based Topical Nanoemulgel for Skin Infection: Formulation and Antibacterial Activity against Staphylococcus aureus and Staphylococcus epidermidis - Ratih Pramuningtyas; Flora Ramona Sigit Prakoeswa; Sri Wahyuni (Journal of Medicinal Plants)
Background: Utilizing pomegranate peel as an antibacterial agent in topical formulations presents an opportunity for optimization through innovative drug delivery systems, notably encapsulating extracts and fractions within a nanoemulgel. Objective: This study aimed to formulate ethanol extract and ethyl acetate fraction of pomegranate peel into nanoemulgels and assess their antibacterial activity against skin disease-causing bacteria. Methods: The methodology encompassed extraction, formulation, testing, and antibacterial assays involving maceration and fractionation using ethanol and ethyl acetate solvents. The physical properties and antibacterial efficacy of the nanoemulgels were evaluated. Results: Nanoemulsions derived from pomegranate peel ethanol extracts and ethyl acetate exhibited promising attributes, demonstrating 98.27 % and 98.77 % transmittance levels and zeta potentials of 0.18 mV and 0.32 mV. The nanoemulgel with ethanol had a pH of 6.62 ± 0.02, 6.86 ± 0.01, 6.3 ± 0.01 in 0.5 %, 1 %, and 1.5 % concentrations. For nanoemulgels with ethyl acetate, the pH levels for concentrations 0.5 %, 1 %, and 1.5 % are 6.58 ± 0.00, 6.80 ± 0.01, and 6.94 ± 0.01, respectively. These nanoemulgels displayed consistent odour, colour, and homogeneity characteristics, highlighting their suitability for topical application. The adhesion, spreadability, and viscosity assessments showed concentration-dependent variations, influencing effectiveness and user comfort. Notably, these nanoemulgels displayed substantial potential as antimicrobial agents against S. aureus and S. epidermidis bacteria in inhibitory assays, signalling promise for addressing skin infections. Conclusion: Overall, the study underscores the potential of nanoemulgels derived from pomegranate peel extracts as a natural alternative for topical antimicrobial therapy against skin infections.